Studies of the possibility to use Gas Pixel Detector as a fast trigger tracking device. Issue 1 (January 2016) - Sinev, N; Bashindzhagyan, G; Korotkova, N; Romaniouk, A; Tikhomirov, V
Abstract: Gas Pixel Detector (GPD) technology offers new possibilities, which make them very attractive for application in existing and future accelerator experiments and beyond. GPDs combine advantages of silicon and gaseous detectors. They can be produced radiation hard and with low power consumption using relatively cheap technology. Low capacitance of the individual pixel channel allows us to obtain a large signal to noise ratio. Using a time projection method for GPD readout one obtains 3D track image with precise coordinate (31 µm) and angular information (0.40°). This feature would allow us to achieve performance of one GPD layer equal to a few layers of silicon detectors. Implementation of a fast readout and data processing at the front-end level allows one to reconstruct a track segment in less than 1 μs, and to use this information for the first level trigger generation. The relevant algorithms of data acquisition and analysis are described and the results of simulations are presented in this paper.